Innovation in wind turbine design - Jamieson, Peter, 1946-; Hassan, Garrad (Hoboken, N.J. : Wiley, 2011)
"Innovation in Wind Turbine Design covers the basics of design and the reasons behind design choices, as well as the methodology for evaluating innovative systems and components, always referencing a state of the art system for comparison. Thus the reader is able to understand current technology and the reasoning behind progress to date, before assessing where it can go in the future. It discusses the basics, as well as how to apply existing engineering knowledge to further technology. Innovation in Wind Turbine Design is divided into three main sections: introduction, design background and technology evaluation. Section 1 reviews the evolution of modern wind technology and establishes the basis for evaluating standard and innovative designs. Section 2 reviews the optimization of rotor design, discusses wind energy conversion systems, drive trains, scaling issues and offshore wind turbines, and concludes with an overview of technology trends with a glimpse of possible future technology. Section 3 comprises a global view of the multitude of design options for wind turbine systems, the basis for comparative valuation and evaluation methodology, cost of energy assessment and includes a number of innovative examples, some from working experiences for commercial clients. Draws upon the author's 30 years industry experience to synergize the separate fields of engineering innovation and wind technology into one practical reference text Enables both creative and analytical thinking as well as engineering insight that is invaluable in the early stages of parametric studies Includes innovative examples from working experiences for commercial clients Includes previously unpublished or little disseminated theory, including the author's recent research solving a problem generalizing Betz' theory to account for the behavior of rotors in ducts or non-uniform flow regions"--
Front Matter -- Introduction -- Design Background. Rotor Aerodynamic Theory -- Rotor Aerodynamic Design -- Rotor Structural Interactions -- Upscaling of Wind Turbine Systems -- Wind Energy Conversion Concepts -- Drive Train Design -- Offshore Wind Turbines -- Technology Trends Summary -- Technology Evaluation. Cost of Energy -- Evaluation Methodology -- Design Themes. Optimum Blade Number -- Pitch versus Stall -- HAWT or VAWT? -- Free Yaw -- Multi Rotor Systems -- Design Themes Summary -- Innovative Technology Examples. Part Introduction -- Adaptable Rotor Concepts -- A Shrouded Rotor -- The Gamesa G10X Drive Train -- Gyroscopic Torque Transmission -- The Norsetek Rotor Design -- Siemens Blade Technology -- Stall Induced Vibrations -- Magnetic Gearing and Pseudo-Direct Drive -- Summary and Concluding Comments -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Wind turbines; TECHNOLOGY & ENGINEERING -- Power Resources -- General; TECHNOLOGY & ENGINEERING -- Mechanical; Wind turbines; Electronic books; Electronic books